Works councils and collective bargaining in Germany: A simple but crucial theoretical extension - Uwe Jirjahn (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2014)
A model by Huebler and Jirjahn (2003) suggests that rent-seeking activities of works councils are more limited in establishments covered by collective bargaining. The model predicts that works councils should have a stronger productivity effect and a weaker wage effect in covered than in uncovered establishments. While empirical studies have provided supporting evidence for the predicted productivity effects, the results on the wage effects of works councils in covered and uncovered establishments are very mixed. This article extends Huebler and Jirjahn's model to reconcile the empirical findings. The extended model takes into account that collective bargaining coverage not only limits the opportunities for rent-seeking activities but also strengthens the effectiveness of performance-enhancing work practices negotiated between employers and works councils. The latter influence of collective bargaining coverage can result in a higher wage effect of works councils in covered establishments.
Keywords: J24; J31; J51; J53; 330; Works Council; Collective Bargaining Coverage; Productivity; Wages